## Step by step solution :

## Step 1 :

Equation at the end of step 1 : ((0 – (2•3×2)) – 17x) – 12 = 0

## Step 2 :

## Step 3 :

Pulling out like terms :3.1 Pull out like factors:-6×2 – 17x – 12=-1•(6×2 + 17x + 12)

Trying to factor by splitting the middle term

3.2Factoring 6×2 + 17x + 12 The first term is, 6×2 its coefficient is 6.The middle term is, +17x its coefficient is 17.The last term, “the constant”, is +12Step-1 : Multiply the coefficient of the first term by the constant 6•12=72Step-2 : Find two factors of 72 whose sum equals the coefficient of the middle term, which is 17.

-72 | + | -1 | = | -73 | ||

-36 | + | -2 | = | -38 | ||

-24 | + | -3 | = | -27 | ||

-18 | + | -4 | = | -22 | ||

-12 | + | -6 | = | -18 | ||

-9 | + | -8 | = | -17 | ||

-8 | + | -9 | = | -17 | ||

-6 | + | -12 | = | -18 | ||

-4 | + | -18 | = | -22 | ||

-3 | + | -24 | = | -27 | ||

-2 | + | -36 | = | -38 | ||

-1 | + | -72 | = | -73 | ||

1 | + | 72 | = | 73 | ||

2 | + | 36 | = | 38 | ||

3 | + | 24 | = | 27 | ||

4 | + | 18 | = | 22 | ||

6 | + | 12 | = | 18 | ||

8 | + | 9 | = | 17 | That”s it |

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step2above, 8 and 96×2 + 8x+9x + 12Step-4 : Add up the first 2 terms, pulling out like factors:2x•(3x+4) Add up the last 2 terms, pulling out common factors:3•(3x+4) Step-5:Add up the four terms of step4:(2x+3)•(3x+4)Which is the desired factorization

Equation at the end of step 3 :

(-3x – 4) • (2x + 3) = 0

## Step 4 :

Theory – Roots of a product :4.1 A product of several terms equals zero.When a product of two or more terms equals zero, then at least one of the terms must be zero.We shall now solve each term = 0 separatelyIn other words, we are going to solve as many equations as there are terms in the productAny solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation:4.2Solve:-3x-4 = 0Add 4 to both sides of the equation:-3x = 4 Multiply both sides of the equation by (-1) : 3x = -4 Divide both sides of the equation by 3:x = -4/3 = -1.333

Solving a Single Variable Equation:4.3Solve:2x+3 = 0Subtract 3 from both sides of the equation:2x = -3 Divide both sides of the equation by 2:x = -3/2 = -1.500

### Supplement : Solving Quadratic Equation Directly

Solving 6×2+17x+12 = 0 directly Earlier we factored this polynomial by splitting the middle term. let us now solve the equation by Completing The Square and by using the Quadratic Formula

Parabola, Finding the Vertex:5.1Find the Vertex ofy = 6×2+17x+12Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up and accordingly has a lowest point (AKA absolute minimum).We know this even before plotting “y” because the coefficient of the first term,6, is positive (greater than zero).Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.Parabolas can model many real life situations, such as the height above ground, of an object thrown upward, after some period of time.

You are watching: Which of the following is a factor of 6×2 + 17x + 12?

See more: 2004 Chevy Cavalier Fuel Filter Location, 2003 04 05 Chevrolet Cavalier & Pontiac Sunfire 2

See more: On A Topographic Map, What Does It Mean When Contour Lines Are Close Together ?

The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to be able to find the coordinates of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is given by -B/(2A). In our case the x coordinate is -1.4167Plugging into the parabola formula -1.4167 for x we can calculate the y-coordinate:y = 6.0 * -1.42 * -1.42 + 17.0 * -1.42 + 12.0 or y = -0.042

Parabola, Graphing Vertex and X-Intercepts :

Root plot for : y = 6×2+17x+12 Axis of Symmetry (dashed) {x}={-1.42} Vertex at {x,y} = {-1.42,-0.04} x-Intercepts (Roots) : Root 1 at {x,y} = {-1.50, 0.00} Root 2 at {x,y} = {-1.33, 0.00}

Solve Quadratic Equation by Completing The Square

5.2Solving6x2+17x+12 = 0 by Completing The Square.Divide both sides of the equation by 6 to have 1 as the coefficient of the first term :x2+(17/6)x+2 = 0Subtract 2 from both side of the equation :x2+(17/6)x = -2Now the clever bit: Take the coefficient of x, which is 17/6, divide by two, giving 17/12, and finally square it giving 289/144Add 289/144 to both sides of the equation :On the right hand side we have:-2+289/144or, (-2/1)+(289/144)The common denominator of the two fractions is 144Adding (-288/144)+(289/144) gives 1/144So adding to both sides we finally get:x2+(17/6)x+(289/144) = 1/144Adding 289/144 has completed the left hand side into a perfect square :x2+(17/6)x+(289/144)=(x+(17/12))•(x+(17/12))=(x+(17/12))2 Things which are equal to the same thing are also equal to one another. Sincex2+(17/6)x+(289/144) = 1/144 andx2+(17/6)x+(289/144) = (x+(17/12))2 then, according to the law of transitivity,(x+(17/12))2 = 1/144We”ll refer to this Equation as Eq. #5.2.1 The Square Root Principle says that When two things are equal, their square roots are equal.Note that the square root of(x+(17/12))2 is(x+(17/12))2/2=(x+(17/12))1=x+(17/12)Now, applying the Square Root Principle to Eq.#5.2.1 we get:x+(17/12)= √ 1/144 Subtract 17/12 from both sides to obtain:x = -17/12 + √ 1/144 Since a square root has two values, one positive and the other negativex2 + (17/6)x + 2 = 0has two solutions:x = -17/12 + √ 1/144 orx = -17/12 – √ 1/144 Note that √ 1/144 can be written as√1 / √144which is 1 / 12

### Solve Quadratic Equation using the Quadratic Formula

5.3Solving6x2+17x+12 = 0 by the Quadratic Formula.According to the Quadratic Formula,x, the solution forAx2+Bx+C= 0 , where A, B and C are numbers, often called coefficients, is given by :-B± √B2-4ACx = ————————2A In our case,A= 6B= 17C= 12 Accordingly,B2-4AC=289 – 288 =1Applying the quadratic formula : -17 ± √ 1 x=—————12So now we are looking at:x=(-17±1)/12Two real solutions:x =(-17+√1)/12=-1.333 or:x =(-17-√1)/12=-1.500